Combustion characteristics of a spark ignition engine operating with liquid lpg injection - Mustaffa, Norrizal (2019)
Issues on global warming, stringent emissions regulation and unstable fuel price are among the primary reasons that lead to the usage of alternative fuels in internal combustion engines. Liquefied petroleum gas (LPG) is one of the most popular alternative fuels for spark ignition (SI) engines that received lots of attention due to its availability and acknowledged superior properties than gasoline. However, detail analysis on latest technology of liquid LPG injection that introduces the fuel in liquid phase during injection is scarcely found. With this motivation, a comprehensive experimental study on an SI engine has been conducted in order to evaluate effects of the liquid LPG injection. A series of experiments was performed at several engine speeds ranging from 1500rpm until 4000rpm with a step size of 500rpm. During the experiments, four throttle position (TP) were tested; 25%, 50%, 75% and 100%. The experimental results between liquid LPG injection and gasoline were compared. It was found that liquid LPG injection has the capability to increase the engine torque and brake power by 9.56% and 8.34%, respectively as compared to gasoline. Since the LPG has lower carbon to hydrogen ratio than gasoline, the reduction of carbon related emissions, CO2 and CO were found lower in LPG operation by 9.15% and 58.55% respectively than gasoline at all testing conditions. Meanwhile, HC and NOx were recorded higher for LPG, compared to gasoline at all testing conditions. Statistical analysis indicates that liquid LPG operation in SI engine exhibited better combustion stability with 14.87% lower coefficient of variation (COV) of maximum in-cylinder pressure peak throughout the testing than gasoline. In addition, liquid LPG injection also showed improvement on the in-cylinder pressure, rate of pressure rise (ROPR) and rate of heat release (ROHR) where the maximum plot of these parameters was found higher with the usage of liquid LPG injection than gasoline.